2017
DOI: 10.5114/ada.2017.67074
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in patients with severe psoriasis

Abstract: IntroductionPsoriasis is a chronic inflammatory skin disease, in which an important role is played by psychological factors.AimTo evaluate the frontal cognitive functions in patients with psoriasis.Material and methodsThe study included 188 subjects (97 patients with psoriasis and 91 healthy controls). To assess the dorsolateral prefrontal cortex functions, the Trail Making Test and the Stroop test were applied. Severity of psoriasis was assessed by means of the PASI index.ResultsCompared to healthy subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Psoriasis cases scored significantly lower on cognitive tests than controls, especially with regard to working memory. While severity of psoriasis was not associated with cognitive function, longer duration of disease dramatically correlated with worse cognitive test results 31 …”
Section: Discussionmentioning
confidence: 76%
“…Psoriasis cases scored significantly lower on cognitive tests than controls, especially with regard to working memory. While severity of psoriasis was not associated with cognitive function, longer duration of disease dramatically correlated with worse cognitive test results 31 …”
Section: Discussionmentioning
confidence: 76%
“…Still, association of psoriasis with psychological, inflammatory, metabolic or other systemic diseases may pose these patients at risk for cognitive impairment [71]. Gisondi [73]. These studies showed differences in design, but psoriasis was an independent risk factor for cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PS patients may suffer from cognitive impairment [37][38][39]. For instance, a recent study on patients with severe PS revealed that they scored lower in neuropsychological tests that assessed working memory and executive function (e.g., the trail-making test, the Stroop color-word interference test, and the Beck Depression Inventory [BDI]) than a healthy control group and independently of depressive symptom severity [37].…”
Section: Evidence For An Association Of Skin Disease With Cognitive Imentioning
confidence: 99%
“…For instance, a recent study on patients with severe PS revealed that they scored lower in neuropsychological tests that assessed working memory and executive function (e.g., the trail-making test, the Stroop color-word interference test, and the Beck Depression Inventory [BDI]) than a healthy control group and independently of depressive symptom severity [37]. In the same study, a longer duration of PS significantly correlated with worse outcomes on measures of working memory and executive function.…”
Section: Evidence For An Association Of Skin Disease With Cognitive Imentioning
confidence: 99%
See 1 more Smart Citation